Comparison of Sexual Risky Factors of Men Who Have Sex With Men and Sex-buying Men as Groups Vulnerable to Sexually Transmitted Diseases - Jung, Minsoo (The Korean Society for Preventive Medicine, 2012)
OBJECTIVES: It is necessary to examine groups carrying out sexually risky behavior because the prevalence of sexually transmitted diseases (STDs) is high among them. In this study, the prevalence of STDs among homosexuals and sex-buying men in South Korea was investigated, along with their sexual risk factors. METHODS: Men who have sex with men (MSMs, n=108) were recruited in Seoul and Busan by applying the time location sampling method, while sex-buying men (n=118) were recruited from a john school in Gyeonggi province, the suburbs of Seoul. Dependent variables included past or present infection with syphilis, Chlamydia, gonorrhea, and human immunodeficiency virus. Independent variables included health behavior, social support, sexual behavior, and safe sex. RESULTS: It was found that when the MSMs were non-drunk while having sexual intercourse (odds ratio [OR], 0.132), they showed a higher STD infection rate when they had a higher number of anal sex partners (OR, 5.872), rarely used condoms (OR, 1.980), had lower self-efficacy (OR, 0.229), and were more anxious about becoming infected with an STD (OR, 3.723). However, the men who paid for sex showed high STD infections when they had more sex partners (OR, 2.286) and lower education levels (OR, 3.028). CONCLUSIONS: STD infections among the two groups were high when they were engaged with many sex partners and not having protected sex. In other words, there was a gap in risky sex behavior within such groups, which was significantly related to the possibility of developing an STD. Therefore, the preventive intervention against STDs for these groups needs to be expanded to include management of sex behaviors.